Gut Microbiome Analyses of Wild Migratory Freshwater Fish (Megalobrama terminalis) Through Geographic Isolation - Liu, Yaqiu; Li, Yuefei; Li, Jie; Zhou, Qiong; Li, Xinhui (Frontiers in Microbiology, 2022)
Gut microbiome was considered as a critical role in host digestion and metabolic homeostasis. Nevertheless, the lack of knowledge concerning how host-associated gut microbiome underpins the host metabolic capability and regulates digestive functions hinders analysis of the gut microbiome diversity in wild populations by environment and geography. In order to explore microbiome variation in diverse geographic populations, we selected the black Amur bream (Megalobrama terminalis) inhabiting southern China drainage with multiple geographic populations and relative high digestive plasticity as a candidate to explore potential effects of genetic variation and environment discrepancy on its gut microbiome. Here, high-throughput 16S rRNA gene sequencing was utilized to decipher the distinct composition and diversity of the entire gut microbiota in wild M. terminalis distributed throughout southern China. The results indicated that mainland (MY and XR) populations exhibited a higher alpha diversity than that of the Hainan Island (WS) population. Moreover, a clear taxon shift influenced by water temperature, salinity and gonadosomatic index in the course of seasonal variation was observed in the gut bacterial community. Furthermore, geographic isolation and seasonal variation significantly impacted amino acid, lipid, and carbohydrate metabolism of fish gut microbiome. Specifically, each geographic population displayed its own unique regulation pattern of gut microbiome was recognized as a specific digestion strategy to enhance adaptive capability in resident environment. Consequently, this discovery suggested that long-term geographic isolation lead to variant environmental factor and genotype, which made synergetic effect on the diversity of the gut microbiome in wild M. terminalis. In addition, the findings provide effective information for further exploring ecological fitness countermeasure in fish population.